2006
DOI: 10.1021/la0621721
|View full text |Cite
|
Sign up to set email alerts
|

HEPES-Stabilized Encapsulation of Salmonella typhimurium

Abstract: Most bacteria, planktonic and sessile, are encapsulated inside loosely bound extracellular polymeric substance (EPS) in their physiological environment. Imaging a bacterium with its capsule requires lengthy sample preparation to enhance the capsular contrast. In this study, Salmonella typhimurium was investigated using atomic force microscopy for a practical means of imaging an encapsulated bacterium in air. The investigation further aimed to determine the relation between the buffers used for preparing the ba… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
30
0

Year Published

2008
2008
2014
2014

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(34 citation statements)
references
References 68 publications
4
30
0
Order By: Relevance
“…This kind of substance, imaged by ambient AFM, especially when it appears around single bacteria (as in our center-intermediate zones), is virtually identical to what has been associated with bacterial capsules in the some other investigations (30,31). When detected in larger quantities (as in our peripheral areas), they have been attributed to EPS produced by the bacteria (25).…”
Section: Resultssupporting
confidence: 80%
See 3 more Smart Citations
“…This kind of substance, imaged by ambient AFM, especially when it appears around single bacteria (as in our center-intermediate zones), is virtually identical to what has been associated with bacterial capsules in the some other investigations (30,31). When detected in larger quantities (as in our peripheral areas), they have been attributed to EPS produced by the bacteria (25).…”
Section: Resultssupporting
confidence: 80%
“…and/or stability, experiments with nonbiological particles (Al 2 O 3 powder) were performed. As the suspending liquid we used KPi buffer, since it produced the liquid-like substances around our S. epidermidis cells, and a HEPES solution, as this buffer has been shown to result in the formation of similar liquid-like substances in other work (31). With KPi as the suspending liquid, both isolated and aggregated alumina particles were found at the center of the spot, with no evidence of any kind of liquid-like substances in this area (Fig.…”
Section: Vol 77 2011 Liquid-wrapped Bacterial Cells Imaged By Afm 3107mentioning
confidence: 97%
See 2 more Smart Citations
“…This result indicates that the presence of HEPES buffer, even in very small concentrations (2 mM in our case), significantly affects the mechanical properties of the capsules. The higher phase contrast observed for bacterial capsules exposed to HEPES buffer is consistent with AFM phase imaging of Salmonella enterica serovar Typhimurium, for which it was observed that rinsing the bacteria with HEPES buffer could stabilize and promote capsule formation (35). It is likely that molecules from the HEPES buffer are trapped in the capsular matrix and may not be completely removed during rinsing with MilliQ water.…”
Section: Discussionsupporting
confidence: 78%